2021
DOI: 10.2147/ijgm.s317350
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Demographic and Clinical Characteristics on Disease Severity and Mortality in Patients with Confirmed COVID-19

Abstract: Background We investigated potential predictive factors for mortality and disease severity from demographic and clinical data, comorbidities, and laboratory findings in patients with confirmed COVID-19 who were consecutively admitted to our tertiary hospital. Methods In this retrospective, single-center, observational study, we enrolled consecutive 540 adult patients who had COVID-19 confirmed by a molecular method. Patients were categorized into three groups based on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…Consequently, the RALE score also positively correlated with the neutrophil-to-lymphocyte ratio, a common prognostic marker of COVID-19 progression ( 20 , 21 ). Overall, these results suggest that COVID-19 severity is accompanied by an elevated neutrophil count and a low lymphocyte count, which is in agreement with recently published data ( 24 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consequently, the RALE score also positively correlated with the neutrophil-to-lymphocyte ratio, a common prognostic marker of COVID-19 progression ( 20 , 21 ). Overall, these results suggest that COVID-19 severity is accompanied by an elevated neutrophil count and a low lymphocyte count, which is in agreement with recently published data ( 24 ).…”
Section: Discussionsupporting
confidence: 93%
“…Although a link between platelet counts and COVID-19 severity has been broadly described, these findings remain controversial. Indeed, while several reports indicated that platelet counts were lower in patients with severe COVID-19 than in peers with mild disease ( 22 24 ), the opposite has also been reported in patients with compromised lung function ( 25 ). We found that the admission platelet counts positively correlated with the RALE score, indicating that patients with a greater degree of compromised lung function have elevated platelet counts.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of any given disease depends on the population's demographic and clinical characteristics [17]. Therefore, we aimed to study these factors to understand COVID-19 in detail.…”
Section: Discussionmentioning
confidence: 99%
“…In all relevant studies, the hemoglobin levels were found to be lower in severe groups than those in controls [7,10,24] or non-severe groups [22,[25][26][27][28][29]. However, in the comparisons between severity [7,10,15,[17][18][19]23,24,[30][31][32][33][34][35][36][37] and mortality [10,30,[38][39][40][41], there was not a consistent numerical magnitude relationship between them. In addition, studies on TIBC [8,10,12,13] and TSAT [8,13] only refer to mortality.…”
Section: Introductionmentioning
confidence: 99%